Geomorphological Hazards - Zêzere, José (2020)
Earthquakes, tsunami, landslides, coastal erosion and floods are major geomorphological hazards in Portugal’s mainland. The earthquakes are concentrated along the Algarve coastal zone and along the west coastal zone, mainly between Sines and the Nazaré Canyon, but also along the Lower Tagus Valley Fault Zone. Strong earthquakes with epicentre in the ocean floor have generated tsunami in the past that affected the southern and western coasts. Landslides are triggered by earthquakes and rainfall. The landslide types and landslide predisposing factors are distinct in the three main geomorphological units in the country. Coastal erosion has been a problem as a consequence of the regressive trend of the coastline associated with accelerated erosion along coastal cliffs and the poor sand supply on sandy beaches. Flood disasters have been widespread along the country, but more critical areas are located in the Lisbon region and the Tagus valley, in the Oporto region and the Douro valley, in the Coimbra region and the Mondego valley and along the Vouga River valley.